2023
DOI: 10.3390/dj11060153
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative and Protective Effects on Dental Tissues of a Fluoride–Silicon-Rich Toothpaste Associated with a Calcium Booster: An In Vitro Study

Abstract: Calcium boosters have been used as a supplement for fluoride toothpastes to repair the dental tissues and reduce dentin permeability. This in vitro study aimed to characterize the regenerative and protective effects of the treatment of dental tissues with a fluoride–silicon-rich toothpaste associated with a calcium booster. Bovine enamel and dentin blocks (n = 5) were obtained (4 × 4 × 6 mm). A fluoride–silicon-rich toothpaste and a calcium booster were used to brush the enamel and dentin both immediately and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
(61 reference statements)
2
4
0
Order By: Relevance
“…A previous study has, however, reported a mineral layer formation on dentin only after 7 days of brushing evaluation using Dentalclean toothpaste [22]. Our results are in line with the previous report demonstrating formation of a remineralizing layer after brushing dentin with Dentalclean toothpaste associated with booster as soon as day 1 [13]. On the other…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…A previous study has, however, reported a mineral layer formation on dentin only after 7 days of brushing evaluation using Dentalclean toothpaste [22]. Our results are in line with the previous report demonstrating formation of a remineralizing layer after brushing dentin with Dentalclean toothpaste associated with booster as soon as day 1 [13]. On the other…”
Section: Discussionsupporting
confidence: 92%
“…Comparable to a previous study [13], the EDX (Tables 2-4) elemental analysis along with the SEM and AFM images demonstrates that treatment with all dentifrices was able to modify the dentinal surface, also justifying the presence of elements such as Ca, F and P. These results lead to the rejection of the first proposed null hypothesis. Dentalclean dentifrice is regarded as a multifunctional phosphate-based dentifrice in an acidified and stabilized phosphate/fluoride complex.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…The results were even more significant in relation to the number of sensitive teeth treated with "pain elimination" after one month of use (69.3%), and only 4% of teeth achieved "no pain reduction", as shown in Table 5. In a previous study [36], it was observed that a considerable mineral change occurred following 5 days of treatment with a booster/silicon-rich toothpaste, forming a protective silicon-enriched mineral layer on both enamel and dentin surfaces. In vitro studies have shown that a fluoride-silicon-rich toothpaste combined with a calcium booster regenerates dental tissues by remineralizing the enamel structure and occluding dentin tubules [36].…”
Section: Discussionmentioning
confidence: 92%